2016
DOI: 10.1371/journal.pone.0167176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glu12-His89 Interaction on Dynamic Structures in HIV-1 p17 Matrix Protein Elucidated by NMR

Abstract: To test the existence of the salt bridge and stability of the HIV-1 p17 matrix protein, an E12A (mutated at helix 1) was established to abolish possible electrostatic interactions. The chemical shift perturbation from the comparison between wild type and E12A suggested the existence of an electrostatic interaction in wild type between E12 and H89 (located in helix 4). Unexpectedly, the studies using urea denaturation indicated that the E12A substitution slightly stabilized the protein. The dynamic structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…It was concluded that the structure in the p17p24N was generally similar to those observed in the current mutant studies. These structural changes may have a negative effect on their biological activity 4 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that the structure in the p17p24N was generally similar to those observed in the current mutant studies. These structural changes may have a negative effect on their biological activity 4 , 36 …”
Section: Discussionmentioning
confidence: 99%